A new insight to the analysis of co-authorship in Google Scholar - Ghazal Kalhor; Amin Asadi Sarijalou; Niloofar Sharifi Sadr; Behnam Bahrak (Applied Network Science, 2022)
Abstract Google Scholar is a search engine for scholarly literature which indexes most academic papers, dissertations, and books that are available online. This paper aims to analyze the characteristics of the manually added co-authorship network (MACN), in which nodes are authors who manually add their collaborators from a list of co-authors suggested by Google scholar based on their joint scholarly work. In addition to this network, we also perform structural analysis on the authors’ fields of interest network (FIN), and their affiliated institute network (AIN). We introduce a new citation metric based on the distribution of authors’ citation count, which captures the position of authors in their research area and can help us in ranking the universities in each scientific field.